Approach to the patient with pregnancy and lactation-associated osteoporosis: A case report and a review of the literature. Issue 46 (November 2017) - Zhang, Min; Chen, Ping; Li, Bin; Du, Juan; Pan, Ting; Chen, Jingyan
Abstract: Rationale: Pregnancy and lactation-associated osteoporosis (PLO) is very rare, but it can cause severe vertebral compression fractures with disabling back pain. Although it is a rare, PLO must be kept in mind in the differential diagnosis in patients presenting with low back pain during or after pregnancy. Patient concerns: A 23-year-old woman who suffered from lumbago and fractures in the vertebral column 1 month after delivery. Diagnosis: Pregnancy and lactation-associated osteoporosis. Interventions: Combination therapy of calcium and vitamin D were used for treatment, as well as regular follow-up. Outcomes: The patient's back pain had decreased significantly, the bone metabolic index, bone mineral density (BMD) had improved and she did not experience any recurrence. Lessons: Early diagnosis and treatment of calcium and vitamin D, as well as the efficacy of PLO intervention monitoring and evaluation are critical for the success of treatment.